Meningkatkan Minat Literasi Baca Kepada Murid UPT SD Negeri 060855 Melalui Adanya Perpustakaan Mini di Kelas - Santa Claudiya Novita Simanjuntak; Hairani Siregar (Pengelola Jurnal Politeknik Negeri Ketapang Jl. Rangga Sentap, Dalong Sukaharja, Ketapang 78813. Telp. (0534) 3030686 Kalimantan Barat, 2023)
Indonesia still ranks lowest in terms of literacy, which is very bad because this cannot be changed even though the government has tried various ways to increase interest in reading and a culture of literacy in Indonesia starting with building the National Library and ordering its people to adopt a reading culture because this is very important for the future and our country. The effect of a lack of literacy or interest in reading on students and students and the ability to think critically is still low. This is also inseparable from the reading culture which is still foreign to Indonesian society. Therefore PKL 1 which was carried out at UPT SD Negeri 060855, was carried out in order to increase reading literacy through having a mini library in class. The helping process was carried out using the groupwork method and the objectives of this activity were stated to have been achieved, as evidenced by the growth of children's enthusiasm for learning and interest in reading.